Determination of the Body Condition Score and Its Relationship with Milk Yield in Turkish Holstein Cows - Aşkın Galiç (Journal of Agricultural Sciences)
It is quite important to keep the condition of cows under surveillance due to conduct of nutritional programs in dairy herds as well as genetic relations with other traits. This study was conducted to estimate the heritability of body condition score (BCS) and genetic correlation with milk yield of Holstein cows. Also, the effects of herd, lactation period and calving age on BCS were investigated. For this aim, body conditions of 1001 cows were scored using the scale of 1-9. The average BCS was determined as 5.52±0.04 and were ranged from 4.54 to 6.58 at different periods of lactation. Results showed that body conditions were affected by the lactation period significantly, while the effects of herd and calving age on BCS were not significant. Estimate of heritability of BCS was 0.20, while the genetic correlation of BCS with milk yield was moderately negative (−0.41) indicating that high-producing cows tend to be leaner. The relationships with other traits currently used to improve type and fertility of animals need to be investigated before including BCS in the selection index of the Turkish Holstein breed.